Macroscopic X-ray Powder Diffraction Scanning, a New Method for Highly Selective Chemical Imaging of Works of Art: Instrument Optimization - Vanmeert, Frederik; De Nolf, Wout; De Meyer, Steven; Dik, Joris; Janssens, Koen (Analytical chemistry (Washington), 2018)
In the past decade macroscopic X-ray fluorescence imaging (MA-XRF) has become established as a method for the noninvasive investigation of flat painted surfaces, yielding large scale elemental maps. MA-XRF is limited by a lack of specificity, only allowing for indirect pigment identification based on the simultaneous presence of chemical elements. The high specificity of X-ray powder diffraction (XRPD) mapping is already being exploited at synchrotron facilities for investigations at the (sub)microscopic scale, but the technique has not yet been employed using lab sources. In this paper we present the development of a novel MA-XRPD/XRF instrument based on a laboratory X-ray source. Several combinations of X-ray sources and area detectors are evaluated in terms of their spatial and angular resolution and their sensitivity. The highly specific imaging capability of the combined MA-XRPD/XRF instrument is demonstrated on a 15th/16th century illuminated manuscript directly revealing the distribution of a large number of inorganic pigments, including the uncommon yellow pigment massicot ( o-PbO). The case study illustrates the wealth of new mapping information that can be obtained in a noninvasive manner using the laboratory MA-XRPD/XRF instrument.